2022
DOI: 10.1111/gbb.12786
|View full text |Cite
|
Sign up to set email alerts
|

Emergent intra‐pair sex differences and organized behavior in pair bonded prairie voles (Microtus ochrogaster)

Abstract: In pair bonding animals, coordinated behavior between partners is required for the pair to accomplish shared goals such as raising young. Despite this, experimental designs rarely assess the behavior of both partners within a bonded pair. Thus, we lack an understanding of the interdependent behavioral dynamics between partners that likely facilitate relationship success. To identify intra-pair behavioral correlates of pair bonding, we used socially monogamous prairie voles (Microtus ochrogaster) and tested bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…We performed fiber photometry to measure GRAB DA -mediated fluorescence as a proxy for extracellular dopamine levels in the nucleus accumbens of voles engaged in operant responding and reward consumption (Fig 1A - C) ( 17 ). We used a previously established social operant task in voles ( 15 ). Voles learned to initially associate rewards with lever pressing through food delivery (Fig S1A - D) before being presented with separate levers that provided transient access to a tethered partner and novel animal (Fig 1D - F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed fiber photometry to measure GRAB DA -mediated fluorescence as a proxy for extracellular dopamine levels in the nucleus accumbens of voles engaged in operant responding and reward consumption (Fig 1A - C) ( 17 ). We used a previously established social operant task in voles ( 15 ). Voles learned to initially associate rewards with lever pressing through food delivery (Fig S1A - D) before being presented with separate levers that provided transient access to a tethered partner and novel animal (Fig 1D - F).…”
Section: Resultsmentioning
confidence: 99%
“…This task is uniquely advantageous in that it separates the appetitive aspect of social reward, reflected in lever pressing and cues predicting social access, from the consummatory aspect of physical social interaction. Furthermore, this task elicits comparable degrees of lever-pressing for both partner and novel voles ( 15 ). Using fiber photometric recordings of the fluorescent dopamine sensor, GRAB DA , we found that anticipation of partner reunion, as well as partner interaction, results in enhanced nucleus accumbens dopamine release compared with the same events directed towards a novel opposite-sex vole.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The formation of stable social groups contributes both to the selectiveness for familiar peers as well as the aggression toward unfamiliar conspecifics, especially following mating (Carter and Getz, 1993;Lee et al, 2019). While there are subtle sex differences in partner preference development, both male and female prairie voles show strong selectivity in their interactions by spending more time with familiar rather than unfamiliar same-sex conspecifics (Brusman et al, 2022). Prairie voles are also often aggressive toward unfamiliar same-sex individuals (Lee et al, 2019;Vahaba et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They provide critical evidence against the idea of potential monomorphism in pair-bonding behaviors in these socially monogamous species. The article by Brusman et al 6 compares indices of pair-bonding in the standard "choice" partner preference test 7,8 and a novel modified non-choice test across two time points between male and female prairie voles.…”
Section: Deepening the Understanding Of Social Bonding And Dynamics O...mentioning
confidence: 99%